Offset layered closure reduces deep wound infection in early-onset scoliosis surgery. Issue 4 (July 2016) - Grzywna, Alexandra M.; Miller, Patricia E.; Glotzbecker, Michael P.; Emans, John B.
Abstract : Deep wound infection is a common complication in early-onset scoliosis (EOS) surgery. Soft tissue technique has received less attention as a means to reduce infection. A retrospective review of 1170 EOS surgeries (single surgeon, institution) investigated the impact of offset layered closure (OLC) and soft tissue awareness. The introduction of OLC reduced deep infection from 3.0% in 99 surgeries to 0.37% in 1071. Logistic regression confirmed that OLC led to significantly lower odds of infection ( P =0.007). This deep infection rate (0.37%) is more typical of elective surgery, providing a more optimistic view of infection in EOS surgery than generally reported.